How Does the Manufacturer Optimize Pricing Decision and Channel Strategy Under Platform Encroachment? - Hao Li; Xin Yuan (Systems, 2025)
The rise of platform competition, driven by the rapid emergence of new e-commerce platforms, has fundamentally reshaped traditional supply chain structures. Under platform encroachment, the manufacturer faces the critical challenge of optimizing their channel strategies to expand market demand and increase profit. To address this, this paper develops a game model considering a manufacturer, a retailer, and two e-commerce platforms (an incumbent and an entrant). The model examines three channel strategies: the single-platform strategy, the synchronous channel strategy, and the reset channel strategy. This paper analyzes how the platform service differentiation and the unit channel setup cost of the manufacturer under the reset channel strategy influence pricing decisions and the manufacturer’s channel strategy. The findings indicate that the synchronous channel strategy yields a higher product price than the reset channel strategy while maximizing dual-platform demand when the extent of platform service differentiation is moderate and the unit channel setup cost is low. Under these conditions, the synchronous and reset channel strategies yield higher expected profits for the manufacturer and retailer than the single-platform strategy. Moreover, the best option for the manufacturer is the synchronous channel strategy when the extent of platform service differentiation is moderate and the unit channel setup cost is relatively high, which achieves a Pareto improvement for all participants. However, the reset channel strategy benefits the entrant platform when the unit channel setup cost is low. The study provides a theoretical foundation for the manufacturers to optimize their channel configurations and effectively adapt to platform competition.